Development of a GIS model for evaluating accessibility of health care facilities in the City of Manila - Apura, Ransie Joy A.
Understanding health care from a geographic perspective is essential in improving the planning and management of health care. One aspect of the health care management is geographic accessibility or the effects of the location of facilities relative to households and other stakeholders on the geographic accessibility of health care. The main objective of this study is to analyze equity and coverage in geographic accessibility provided by health care facilities such as public and private hospitals, public health centers, and attached lying-in clinics. This study uses healthcare facility, population, road network, and secondary data (i.e., poverty incidence, population density, and road density) for the City of Manila. Equity and coverage are evaluated using three criteria: Spatial Equity- distribution of potential access to facilities across prospective users as quantified by the Gini coefficient (0 to 1 scalar measure of inequality); Service Coverage - comparison of calculated extent of service area and provided spatial coverage capacity; and Referral Network- facility-to-facility spatial distribution and its corresponding functional hierarchy capacity. Quantitative measure for each criteria uses estimated travel time/driving time as measurement proxy, applies a prescribed time period in its closest facility analysis, and run with different travel scenarios accounting for varying nature of road traffic in the study site: Scenario 1 - travel time/driving time is 100% of maximum allowable speed for all road segments; Scenario 2- travel time/driving time is 60% of maximum allowable speed for all road segments; and Scenario 3 - 20% of maximum allowable speed for all road segments; and Scenario 4 - 20% of maximum allowable speed for primary road segments. The results of the study indicate that varying road traffic conditions affects equity, referral availability, and service coverage of health care facilities within the geographic travel standard. Scenario 1 (all road segments at 100% maximum allowable speed, scenario 2 (all road segments at 60% maximum allowable speed, and scenario 4 (primary road segments at 20% maximum allowable speed) have high geographic accessibility while scenario 3 (all road segments at 20% maximum allowable speed) has low geographic accessibility. Resulting non-zero Gini coefficients/ inequality values (0.27 to 0.85) of all health care facilities across all districts are acceptable for the first three aforementioned scenarios. All health care facilities for scenario 1, 2, and 4 provide 78% to 100% effective coverage of the study site with all health centers and lying in clinics within 30 minutes of any hospitals and all hospitals are within 30 minutes of one another. For scenario 3: only public health centers have acceptable inequality values across all districts; Gini coefficients for general hospitals and mother & child hospitals are not acceptable; hospitals have low effective coverage (0% to 4%) in some districts of the study site; health centers and lying-in clinics are within 30 minutes of at least one general hospital (level 1 or level 2 or level 3) and specialty, level 1 and level 2 hospitals are within 30 minutes of at least one level 3 hospital. The results also indicate that level 3 hospitals are end referrals hence, proximity (within geographic travel standard) of all other health care facilities to at least one is recommended. Some potential for improvement is also indicated.